Spironolactone 25 mg tablets prescription in Primary Care - Eliezer Alemán-Fernández (Revista Electrónica Dr. Zoilo E. Marinello Vidaurreta, 2023)
Background: resistant arterial hypertension is a major health problem of complex management. The new clinical practice guidelines of the European Society of Hypertension and the European Society of Cardiology recommend the use of spironolactone, an aldosterone receptor antagonist, as the fourth drug in patients with HRT.